Attitudes toward protective behavioral strategies: Do they predict use of strategies and alcohol outcomes over time?. (December 2018) - Grazioli, Véronique S.; Lewis, Melissa A.; Fossos-Wong, Nicole; Larimer, Mary E.
Abstract: Whereas past research among young adults has established that the use of protective behavioral strategies (PBS) is negatively related to alcohol outcomes, fewer studies have examined constructs related to PBS use. This study aimed to examine longitudinally the associations of attitudes toward PBS with PBS use and alcohol outcomes, as well as between PBS use and attitudes toward PBS. It also aimed to examine biological sex as a moderator of these associations. Participants ( N  = 248) were young adults participating in a longitudinal study in the US. Measures of attitudes toward PBS, PBS use, alcohol use and related consequences at 18, 24 and 30-months were included in the analyses. Results indicated that attitudes toward PBS were positively related to subsequent PBS use when prior PBS use was not controlled for; similarly, PBS use was positively related to attitudes toward PBS when prior attitudes were not taken into account. Both associations did not remain significant after controlling for prior PBS use and attitudes. These associations were not significantly moderated by biological sex. There was, however, a significant interaction between attitudes toward PBS and biological sex in predicting alcohol use, such that positive attitudes toward PBS were significantly related to fewer drinks over time among males but not among females, even after controlling for prior PBS use and alcohol use. Finally, after controlling for prior PBS use and consequences, attitudes toward PBS were not significantly related to consequences over time. Implications of these findings for prevention among young adults are discussed. Highlights: Attitudes toward PBS were related to future PBS use when prior PBS use was not controlled for. PBS use was related to subsequent attitudes toward PBS when attitudes were not controlled for. These associations were not significantly moderated by biological sex. Positive attitudes toward PBS were related to fewer drinks among males but not among females. Attitudes toward PBS were not significantly associated with alcohol-related consequences.